ANALISIS STRUKTUR MODAL TERHADAP PENINGKATAN KINERJA KEUANGAN PADA PT. SEMEN TONASA KABUPATEN PANGKEP - Nurlaela Nurlaela (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
This research was conducted to find out that the capital structure can improve financial performance at PT. Semen Tonasa Pangkep. The method of research is field research (field research) and library research (library research). The data used is derived from the financial statements. Semen Tonasa 2011-2015. The results showed that each year has increased its capital structure which in 2011 amounted to 13.87%, 2012 amounted to 19.75%, 2013 by 50.57%, 2014 to 110.56%, and in 2015 amounted to 137.16%. This gives a picture that the investor invested capital is returned in accordance with the time. Current ratio in 2011-2015 was in good condition because it is above the minimu standard, in 2014-2015 the condition is not good. Quick ratio PT. Semen Tonasa be in good shape for being above the common standard of 100%. Debt to Asset Ratio in 2011-2013 were in good condition, in 2012-2015 the condition is not good because it is above the general standard of 50%. Debt to Equity Ratio PT. Semen Tonasa the year 2011 in good condition because it is below the general standard of 50%, in 2012 to 2015 are in poor condition. Return On Investment PT. Cement 20011-2012 Tonasa year the situation is quite good because of increased However the years 2014-2015 decreased which indicates the situation is less good. Return On Equity Company in 2011-2013 are in a good state because of an increase but in 2014-2015 has decreased. Total Asset Turnover PT. Semen Tonasa good condition for the period 2011-2012 had more than 1 time turnover per year, but the year 2013 to 2015 are considered unfavorable. 2011-2013 Year Fixed Asset Turnover condition PT. Semen Tonasa are in good condition, but the years 2014-2015 Fixed Asset Turnover condition is considered unfavorable because the total turnover of fixed assets of less than 1 time per year